REVITALISASI METODE DAN PERAN LEMBAGA BAHTSUL MASA’IL NAHDLATUL ULAMA (LBMNU) DALAM MENJAWAB PERSOALAN KEBIJAKAN PUBLIK - Sam’ani Sya’roni (Jurnal Penelitian, 2010)
The existence of a big national Islamic social mass organization like NU, are getting involved with social, economic, politic, and state’s problems and issues, including public policy. It was convinced that NU-neese’s attitude and activity are related with their organization’s view. As a social mass organization, NU has an interest in struggling social civil welfare, but as Islamic organization, its actions, must be based on religious legitimacy (fiqh). By taking the purposes of welfare, NU -- with its subordinate organization LBMNU-- uses fiqh as a tool to reach social, politics and state goals. This view uttered the new species of fiqh, such an anti-corruption, ecology, or human trafficking. Based on the view, to aim the problem resolution of public policy, LBMNU has been revitalized the method and role of fiqh. The research has been done using qualitative method and Islamic normative approach (ushul fiqh). The data were obtained through library research as the primary one trough content analysis model.